New species of the genus Oligoneuriella Ulmer, 1924 (Ephemeroptera: Oligoneuriidae) from Turkey - Sroka, Pavel; Bojková, Jindřiška; Soldán, Tomáš; Godunko, Roman J (Zootaxa, 2015)
Three new species of the genus Oligoneuriella Ulmer, 1924 from Turkey are described, namely Oligoneuriella magna sp. nov., Oligoneuriella paulopilosa sp. nov. and Oligoneuriella pectinata sp. nov. Differential diagnostic characters are given with regard to the previously known Oligoneuriella species. Data on the affinities, biology, and distribution of the new species are also provided. New morphological characters (setation of mouthparts and gill plates) potentially useful for the taxonomy of the genus are introduced.
Keywords: Ephemeroptera; Animals; velikost těla; Turecko; anatomické struktury zvířat; Animal Structures; zvířata; mužské pohlaví; Body Size; velikost orgánu; Female; Male; rozšíření zvířat; Animal Distribution; ženské pohlaví; Organ Size; Turkey